Learning strategy for senior high school chemistry based on starter experiment approach for improving students’ participation and achievement in learning - I Wayan Subagia; I Gusti Lanang Wiratma (Jurnal Pendidikan dan Pengajaran, 2019)
This paper aimed at describing and explaining chemistry learning strategy for senior high school students based on starter experiment. This learning strategy was developed through research and development (R&D) accommodated from Borg and Gall. The learning strategy consists of three main parts, namely: learning theory, social situation, and syntax. The learning theory used for developing this learning strategy are behavioristics, cognitive constructivist, and social constructivist learning theories. The social situation explains the role of teachers, students, and schools in the implementation of learning strategy: teachers play a role as learning manager, students play a role as active learners, and schools play a role as learning facilities provider. The syntax consists of three main steps, namely observation, concept formulation, and concept application. The observation step consists observation of macroscopic phenomena of matter, writing of observation results, and formulation of questions conducted individually by students. These activities are followed by the discussion of observation results, questions formulation, and question answers conducted by students in groups. The concept formulation and application are also conducted by students in groups based on the task given by the teacher. Therefore, it can be mentioned that this learning strategy involved individual dan group learning of students focused on student centre learning activities. It is believed that this learning strategy can be used to enhance students’ participation and achievement in learning.